SOME DEFECTS OBSERVED IN THE COOPERATION OF PARENTS AND EDUCATORS IN EDUCATION OF PRESCHOOL CHILDREN AND THEIR ANALYSIS (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
It is known that the cooperation of parents and educators of preschool educational institutions is of great importance in the upbringing of preschool children. This article talks about some defects, misunderstandings, shortcomings and problems that arise in the process of cooperation, and offers suggestions, conclusions, and research results as solutions to some problems. Also, a number of details and characteristics of children that the educator should pay close attention to in the process of education are mentioned. Taking into account that the pre-school period is an important period in the decision-making and development of child education, it has its own appearance, the author's thoughts and research is included in this article. Including the analysis of the literature on this topic.